Relationship between Media Access and Social Support with Contraception Plans in East Java, Indonesia - Tasya Azelya Putri Andiani; Muthmainnah, Muthmainnah; Iswari Hariastuti; Yuli Puspita Devi (Indian Journal of Forensic Medicine & Toxicology, 2022)
Objectives: The percentage of contraceptive prevalence rate (CPR) and total fertility rate (TFR) of woman were indicators of the 2015-2019 National Medium Term Development Plan (RPJMN). Total fertility rates in East Java had decreased significantly from 1971 to 2018. The achievement of the prevalence of modern contraceptive use (CPR) in East Java was 63.1 percent based on the results of the Program Performance and Accountability Survey (PPAS, 2018). This achievement was far better than the national achievement which only reached 57 percent. However, this target cannot be achieved by all districts and cities in East Java. According to Green’s theory, the factors of predisposing, enabling and reinforcing are factors that can be related to behavior. The purpose of this study was to analyze the relationship between enabling factors (media access) and reinforcing factors (social support) related to contraceptive plans in women of childbearing age in East Java, Indonesia.Study Design: This research was a non-reactive study using data from the IDHS (Indonesia Demographic and Health Survey) 2017. The unit of analysis in this study was all teenage respondents in East Java who met the requirements of the 2017 IDHS respondents.Results: The results showed that the enabling factor associated with contraception selection plans was listening to information about contraception through radio (sig = 0.038), television (sig < 0.001) and newspapers (sig < 0.001). While the reinforcing factor associated with contraceptive selection plans was supports from health facilities (sig = 0.000) and from farmacy (sig = 0.023). The role of health workers was very minimal in providing information access to woman in the process of selecting contraception. It can be seen that almost all of the woman said that they did not get information either from field officers (41.91%), from health facilities (39.45%), from village clinics (42.52%), and from pharmacists (38.00%).Implication to the fields: Based on the results of this study, there is a need for equal distribution of education in the selection of contraceptive methods to woman through optimizing the role of various health facilities, one of them through contraception officers, optimizing the use of mass media, especially television, radio and newspapers and magazines in disseminating information related to family planning.